2008
DOI: 10.1038/ncb1732
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 mediates neuronal survival through PIKE-L interaction with the dependence receptor UNC5B

Abstract: Netrins, a family of secreted molecules, play critical roles in axon guidance and cell migration during neuronal development 1,2. In addition to its role as a chemotropic molecule, netrin-1 also acts as a survival factor 3-7 . Both UNC5 (i.e. UNC5A, B, C or D) and DCC are transmembrane receptors for netrin-1 8 ,9. In the absence of netrin-1, DCC and UNC5 act as dependence receptors and trigger apoptosis 3,6, 10 . However, how netrin-1 suppresses the apoptotic activity of the receptors remains elusive. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 30 publications
6
104
1
1
Order By: Relevance
“…In the presence of netrin-1, the multimerized receptors recruit different adapter proteins and activate PI3K/Akt, ERK1/2, and small GTPase RhoA/Rac-1/Cdc-42 to affect cell survival, motility, invasion, and morphogenesis through cytoskeletal rearrangements (22)(23)(24). It is reported that PP1A acts downstream of RhoA in LPA-induced YAP dephosphoryaltion (25) and PI3K and ERK1/2 signaling is involved in the regulation of PP1A activity in cancer cells (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of netrin-1, the multimerized receptors recruit different adapter proteins and activate PI3K/Akt, ERK1/2, and small GTPase RhoA/Rac-1/Cdc-42 to affect cell survival, motility, invasion, and morphogenesis through cytoskeletal rearrangements (22)(23)(24). It is reported that PP1A acts downstream of RhoA in LPA-induced YAP dephosphoryaltion (25) and PI3K and ERK1/2 signaling is involved in the regulation of PP1A activity in cancer cells (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The essential functions of PIKE in neuronal survival, development, synaptic plasticity, and memory formation have been clearly demonstrated in our previous reports (8)(9)(10)(11)(12)16). Accumulating evidence suggests that oligodendroglia also plays critical roles in governing neuronal functions, for example, via myelination-dependent saltatory conductance and proper signal transmission in the brain, which is essential for cognitive and motor behaviors (27).…”
Section: Discussionmentioning
confidence: 99%
“…As such, ablation or inactivation of PIKE-L might block the extracellular factors from using this pathway to initiate OL maturation and myelination. We have shown previously that PIKE-L is a downstream effecter of netrin 1 to protect neurons from apoptosis through substantiating the activity of PI3K/Akt (9). Given that netrin 1 also regulates OPC migration and differentiation (34), PIKE-L may be an executor of netrin 1 to promote OL differentiation.…”
Section: Ol-derived Integrin and Axon-derived Lamin That Activates Akmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that attractive and repulsive guidance cues dictate post-stroke axonal sprouting as well as migration of neuroblasts towards the site of the injury (Carmichael, 2008). Netrin-1 overexpression promotes neuronal migration and aids cell survival (Tang et al, 2008). Thus, EGb 761-mediated over-expression of netrin-1 signifies its ability to promote a suitable environment for the migration of neuroblasts.…”
mentioning
confidence: 99%